Analysis of the Use of the Term 'Widow' and Its Impact on the Electability of the Rido Candidate Pair in the Jakarta Regional Election Through the Shannon-Weaver Communication Model - Henry T. Sianipar; Fitri Sarasati; Hamzah Ramadhan; Tri Wahyuti (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
The candidates for Governor and Deputy Governor of DKI Jakarta 2024, Ridwan Kamil and Suswono (RIDO), utilized the Shannon-Weaver communication model. The controversy began with Suswono's statement suggesting that